A. (x-2)-(2-x)=
b. (a+b)+(2a-b)-(a-2b)=
c. (3x-y+1)-(x+y)+(y-x)=
d. -(2a²-3ab)-(2b-3a²)+(-ab-b)=
__
e. 4x-(x+6)+4 dla x= 1/3
f. (x²+1)-(x²-2)+10 dla x=2,2
g. (a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
h. (-a²+2ab-1)+(a²-4ab+5) dla a=1/4 i b=2

1

Odpowiedzi

2010-02-16T21:45:20+01:00
^-do kwadratu

a. (x-2)-(2-x)=x-2-2+x=2x-4

b. (a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=2a+2b

c. (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1

d. -(2a²-3ab)-(2b-3a²)+(-ab-b)=-2a^+3ab-2b+3a^-ab-b=a^+2ab-3b

e. 4x-(x+6)+4 dla x= 1/3
4*1/3-(1/3+6)+4=4/3 - 6 1/3+4=4/3-19/3+4=-15/3+4=-5+4=-1

f. (x²+1)-(x²-2)+10 dla x=2,2
(2,2^+1)-(2,2^-2)+10=(4,84+1)-(4,84-2)+10=5,84-2,84=3+10=13

g. (a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
(-0,1+4*0,2)-(5+2*(-0,1))-(3*0,2-5)=(-0,1+0,8)-(5+(-0,2))-(0,6-5)=0,7-4,8-(-4,4)=-4,1+4,4=0,3

h. (-a²+2ab-1)+(a²-4ab+5) dla a=1/4 i b=2
(-(1/4)^+2*1/4*2-1)+((1/4)^-4*1/4*2+5)=(-1/16+4-1)+(1/16-2+5)=(-1/16+3)+(1/16-7)=(-1/16+3/1)+(1/16-7/1)=(-1/16+48/16)+(1/16-112/16)=47/16+(-111/16)=2 15/16 - 6 15/16=-4